Revenue Recognition According to International Standards – Similarities and Differences - Izabela EMERLING; Małgorzata BIAŁAS (Communications of International Proceedings, 2023)
Revenues are one of the most important concepts in accounting, and their recognition is particularly important according to various standards, because they affect the amount of benefits achieved, and thus shape the financial result. An important aspect in accounting is the moment of achieving revenues and their recognition. Revenue is considered to have accrued when a revenue-generating event occurs in the enterprise, and the recognition of revenue means its inclusion in the balance sheet. In the literature on the subject, we can find publications on the principles of revenue recognition and their impact on the financial statements of business entities. There are also publications on the recognition of revenues according to various standards and their impact on the financial results and thus on the financial condition of the company.  The aim of the paper is to present the principles of recognizing revenues according to US GAAP and IFRS and to analyze how recognized revenues according to various standards will affect the financial result. The research methods used are based on the  studies of professional articles and legal acts, including  Accounting Standards and relevant IAS/IFRS and US GAAP and the presentation of the income statement according to US GAAP and IFRS, as well as an analysis of what revenues have been taken into account and how they affect the financial result.
Keywords: accounting; revenue; recognition; standards